2018
DOI: 10.1007/s00024-018-1943-5
|View full text |Cite
|
Sign up to set email alerts
|

Ground Motion in Kuwait from Regional and Local Earthquakes: Potential Effects on Tall Buildings

Abstract: In recent years, the construction of tall buildings has been increasing in many countries, including Kuwait and other Gulf states. These tall buildings are especially sensitive to ground shaking due to long period seismic surface waves.Although Kuwait is relatively aseismic, it has been affected by large (Mw > 6) regional earthquakes in the Zagros Fold-Thrust Belt (ZFTB). Accurate ground motion prediction for large earthquakes is important to assess the seismic hazard to tall buildings. In this study, we first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The vibrational modes of the Al-Hamra Tower have been determined by ambient noise monitoring at the 80th floor of the building and GPS measurements at the 86th floor. The most prominent modes are North/South with a period of 7.1 sec, East/West 5.7 sec period and a torsional model with 3.1 sec period (Toksöz et al, 2018). Similar mode periods are obtained from both ambient noise monitoring on the 80 th floor and GPS measurements on the 86th floor.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…The vibrational modes of the Al-Hamra Tower have been determined by ambient noise monitoring at the 80th floor of the building and GPS measurements at the 86th floor. The most prominent modes are North/South with a period of 7.1 sec, East/West 5.7 sec period and a torsional model with 3.1 sec period (Toksöz et al, 2018). Similar mode periods are obtained from both ambient noise monitoring on the 80 th floor and GPS measurements on the 86th floor.…”
Section: Introductionsupporting
confidence: 68%
“…The Mw 7.3 earthquake was recorded by the Kuwait National Seismic Network (KNSN) operated by the Kuwait Institute for Scientific Research (KISR) (Gu et al, 2018). The KNSN consists of six broadband stations (KB, MI, QR, RD, RS and UM) and two short-period stations (AB and SA) (Gu et al, 2017).…”
Section: Seismic Sites and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The Kuwait National Seismic Network (KNSN) records local, regional and global earthquakes that occur in Kuwait and in the Globe. The KNSN has main center at Kuwait Institute of Scienti c Research (KISR) and 8 eld seismic stations distributed all over Kuwait (Abd el-aal et al 2020a; Gu et al 2018). This network has a very great impact in protecting modern urban development in the State of Kuwait.…”
Section: Introductionmentioning
confidence: 99%
“…With rapid urbanization and fast‐growing population, an increasing number of super high‐rise buildings with complex configurations and innovative structural systems have been built in megacities around the world . Although most of the skyscrapers are located in cities with low or moderate seismicity, such as Dubai, Shanghai, Shenzhen, and Hong Kong to name a few, recent studies revealed that long‐period ground motions from distant large‐magnitude earthquakes could cause great impact on the safety and functionality of high‐rise buildings . This is because long‐period ground motions could induce the resonance of high‐rise buildings and cause local damages to key structural components.…”
Section: Introductionmentioning
confidence: 99%